Standardized low-resolution electromagnetic tomography of preattentive auditory discrimination in accumulative drinker - Sittiprapaporn, Phakkharawat (Asian Journal of Medical Sciences, 2020)
Background: The present study proposes a task-dependent hypothesis in which the phonological units of segmental (e.g., consonant and vowel) and suprasegmental (e.g., prosodic) are processed in discrete asymmetry of the human brain. Although the left hemisphere (LH) is selectively employed for processing linguistic information irrespectively of acoustic cues or subtype of phonological unit, the right hemisphere (RH) is employed for prosody-specific cues.Although the left hemisphere is selectively employed for processing linguistic information irrespectively of acoustic cues or subtype of phonological unit, the right hemisphere is employed for prosody-specific cues. Aims and Objective: As both hemispheres are lateralized for speech and language, the objective of this study is to extend the investigation of how the pre-attentive processing of vowel duration changes of Thai monosyllabic words in alcoholic drinkers. Materials and Methods: Forty healthy right-handed adults participated in this study. Results: This study found that both rising-to-falling and falling-to-rising tone changes perception elicited MMN between 245-297 msec with reference to the standardstimulus ERPs. The long-to-short and short-to-long vowel duration changes elicited a strong MMN for both groups. Source localization was obtained in the Middle Temporal Gyrus (MTG) of the left hemisphere (LH) for both groups. Conclusion: Automatic detection of changes in contour tones is a useful index of language universal auditory memory traces.